Learning Loss Dynamics in Grade II Islamic Education Learning at SD Muhammadiyah Pahandut Palangka Raya - Tu’aini Tu'aini; Romelah Romelah (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The loss of learners' ability to receive knowledge transfer from teachers during the learning process is called learning loss. This phenomenon can cause the loss of students' abilities in the cognitive, affective, and psychomotor domains. This study aims to look at learning loss in PAI learning at Muhammadiyah Pahandut Elementary School in Palangka Raya City. The research method used is a case study with a descriptive qualitative approach and field research. Data collection techniques were observation, interview, and documentation. While data analysis techniques use source triangulation, data validation techniques include data collection, reduction, presentation and conclusion drawing. Based on the results of this study, it was found that there was a learning loss, there were students who were not fluent in reciting the Koran, difficulty in writing Hijaiyah letters and difficulty understanding PAI learning materials related to Jurisprudence material.